2012
DOI: 10.1891/0886-6708.27.4.512
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Trauma Exposure on Community Violence Exposed Adolescents

Abstract: Previous research has documented an association between adolescent community violence (CV) exposure and poor psychological functioning. The purpose of this study was to delineate the relations of adolescent CV, parent trauma exposure (PTE), and adolescent internalizing and externalizing symptomatology while controlling for adolescent-reported home violence and parental self-reported posttraumatic stress disorder (PTSD). Participants consisted of 101 pairs of junior high school and high school students and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…There is also evidence that parental PTSD adversely impacts children’s emotion regulation capacity, such that children display decreased distress tolerance and increased emotional reactivity (Bosquet Enlow et al, 2011; Pat-Horenczyk et al, 2015; Samuelson & Cashman, 2008). The association between parental PTSD and adverse child behavioral outcomes has been observed in infants and young children (<5 years; Bosquet Enlow et al, 2011; Pat-Horenczyk et al, 2015), as well as in older children and adolescents (Samuelson & Cashman, 2008; Self-Brown et al, 2012).…”
mentioning
confidence: 99%
“…There is also evidence that parental PTSD adversely impacts children’s emotion regulation capacity, such that children display decreased distress tolerance and increased emotional reactivity (Bosquet Enlow et al, 2011; Pat-Horenczyk et al, 2015; Samuelson & Cashman, 2008). The association between parental PTSD and adverse child behavioral outcomes has been observed in infants and young children (<5 years; Bosquet Enlow et al, 2011; Pat-Horenczyk et al, 2015), as well as in older children and adolescents (Samuelson & Cashman, 2008; Self-Brown et al, 2012).…”
mentioning
confidence: 99%
“…Mental health can be detrimentally affected by witnessing of violent acts, or knowledge of violence in their neighbourhoods, in addition to direct experience of violence (Self-Brown et al 2012). Whether in the heart of cities, or on their perimeters, they are likely to live in neighbourhoods with limited access to healthy food, health and social services, high levels of traffic-related pollution, limited green space, and poor safety, etc.…”
Section: Built Environmentmentioning
confidence: 99%
“…Adolescents may be influenced by their parents’ socioeconomic circumstances (poverty, low education level, and inadequate attention) and factors such as parental conflict, a weak relationship between the parents, domestic violence, and divorce or separation. 20 In addition, the parents’ problem‐solving methods, inadequate discipline, violence between the parents, and child maltreatment (including exclusion, beating, scaring, and suppressing) and neglect can also affect development. 20 Studies have shown that adolescents exposed to domestic and intra-family violence can reproduce this violent behavior.…”
Section: Introductionmentioning
confidence: 99%
“… 20 In addition, the parents’ problem‐solving methods, inadequate discipline, violence between the parents, and child maltreatment (including exclusion, beating, scaring, and suppressing) and neglect can also affect development. 20 Studies have shown that adolescents exposed to domestic and intra-family violence can reproduce this violent behavior. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%